Severe necrosis of the glans penis associated with calciphylaxis treated by partial penectomy. Issue 4 (26th May 2020) - Tezuka, Masato; Mizusawa, Hiroya; Tsukada, Manabu; Mimura, Yuji; Shimizu, Takaaki; Kobayashi, Aya; Takahashi, Yasufumi; Maejima, Toshitaka
Abstract : Introduction: Calciphylaxis is characterized by marked vascular calcification and painful skin ulcers, and it has a poor prognosis. Case presentation: The patient was a 72‐year‐old male. He was referred for penile pain. He had a 4‐year history of dialysis therapy under a diagnosis of diabetic nephropathy. Black and yellow necrosis was observed involving the entire glans, accompanying severe pain. Computed tomography revealed marked calcification involving the thoracoabdominal aorta to iliac arteries, the dorsal artery of the penis and the corpus cavernosum, leading to a diagnosis of calciphylaxis. Penile pain gradually exacerbated and partial penectomy was performed. After surgery, penile pain promptly subsided. Pathological examination confirmed marked calcification of the microvascular wall and narrowing of the lumen. Conclusion: We reviewed 15 Japanese patients with calciphylaxis who had undergone penile surgery. Surgical treatment was considered to be effective at relieving penile pain, but the prognosis remained poor.